Video‐assisted thoracoscopic surgery versus open thoracotomy for resection of lung metastasis—A meta‐analysis of reconstructed time‐to‐event data - Felipe S. Passos; Pedro B. Bregion; Luca Fazzini; Hristo Kirov; Tim Sandhaus; Patrick vonSamson; Torsten Doenst; Tulio Caldonazo (Thoracic Cancer)
Abstract This study aimed to conduct a systematic review and meta‐analysis comparing video‐assisted thoracoscopic surgery (VATS) and open thoracotomy (OT) in the context of pulmonary metastasectomy. Three databases were assessed. The primary outcome was overall survival. The secondary outcomes were recurrence‐free survival, ipsilateral recurrence, and hospital length of stay (LOS). Hazard ratios (HRs), odds ratios (ORs), and mean difference (MD) with 95% confidence intervals (CIs) were calculated. Reconstruction of time‐to‐event data and sensitivity analyses were performed for the primary endpoint. After screening, 11 studies were included encompassing 2159 patients undergoing lung metastasectomy (VATS: 827; OT: 1332). Compared to OT, patients who underwent VATS had higher overall survival rates (HR 0.75; 95% CI 0.67–0.85; p < 0.01), no significant difference in recurrence‐free survival (HR 1.07; 95% CI 0.88–1.29; p = 0.48), shorter hospital LOS (MD −1.99 days; 95% CI −2.59 to −1.39; p < 0.01), and no significant difference in ipsilateral recurrence rates (OR 0.86; 95% CI 0.52–1.42; p = 0.56). For patients undergoing pulmonary metastasectomy, VATS strategy is associated with higher survival rates and reduced hospital LOS when compared with OT. Moreover, metastasis recurrence does not seem to be associated with long‐term mortality in this population.